FACEBOOK DAN PORTAL BOLA.COM: KAJIAN ALTMETIRCS Facebook and Portal Bola.com: Altmetrics Review - Febriyanti Bifakhlina; Imas Sukaesih Sitanggang; Sulistyo Basuki (Jurnal Pustakawan Indonesia, 2017)
AbstractInformation is disseminated to society through the media. Altmetrics is a new study on measurement based on social media utilization in the process of analyzing and informing an article. Most of the studies that use Altmetrics as a measuring tool are studies on scientific publication. This study applied the Altmetrics approach to study the performance of the news website Bola.com. The purpose of this study is to perform an analysis based on Facebook data share to know the popularity of Bola.com website and analyze correlation between Altmetrics Facebook data and pageview of website Bola.com. This study calculated coverage of Facebook for news published on January – May 2016. The result shows that coverage analysis of Facebook in April increased compared toother months. The result also shows that the correlation between Altmetrics Facebook data and pageview is 0.5 that means moderatecorrelation. Most correlations analyzed are positive which means the relationship between content shared on Facebook has a positiverelationship with pageviews produced by Bola.com.Keywords: Altmetrics, Facebook, Social Media, Website Bola.com